2017
DOI: 10.1074/jbc.m116.754127
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Pyruvate Dehydrogenase Kinase 4 in the Heart through Degradation by the Lon Protease in Response to Mitochondrial Substrate Availability

Abstract: Edited by George N. DeMartinoCardiac metabolic inflexibility is driven by robust up-regulation of pyruvate dehydrogenase kinase 4 (PDK4) and phosphorylation-dependent inhibition of pyruvate dehydrogenase (PDH) within a single day of feeding mice a high fat diet. In the current study, we have discovered that PDK4 is a short lived protein (t1 ⁄ 2 ϳ 1 h) and is specifically degraded by the mitochondrial protease Lon. Lon does not rapidly degrade PDK1 and -2, indicating specificity toward the PDK isoform that is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 30 publications
2
54
0
Order By: Relevance
“…It has been recently recognized that the increase in PDK4 protein levels is extremely rapid and occurs within the first day when feeding mice a high‐fat diet (Crewe et al. 2013, 2017). Likewise, the turnover of malonyl‐CoA, the allosteric inhibitor of CPT1, is very rapid in the heart (Reszko et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recently recognized that the increase in PDK4 protein levels is extremely rapid and occurs within the first day when feeding mice a high‐fat diet (Crewe et al. 2013, 2017). Likewise, the turnover of malonyl‐CoA, the allosteric inhibitor of CPT1, is very rapid in the heart (Reszko et al.…”
Section: Discussionmentioning
confidence: 99%
“…PDH is an important metabolic control point where the competition between carbohydrates and fatty acids as metabolic substrates is rapidly regulated in the heart (Lopaschuk et al 2010). It has been recently recognized that the increase in PDK4 protein levels is extremely rapid and occurs within the first day when feeding mice a high-fat diet (Crewe et al , 2017. Likewise, the turnover of malonyl-CoA, the allosteric inhibitor of CPT1, is very rapid in the heart (Reszko et al 2001), given the high expression of acetyl-CoA carboxylase (responsible for its synthesis) and malonyl-CoA decarboxylase (responsible for its degradation).…”
Section: Discussionmentioning
confidence: 99%
“…PDK4 degradation would therefore be essential to reduce PDK4 content upon return to a control diet. Evidence for such a pathway is provided by our previous findings that PDK4 has a short half-life relative to other PDK isoforms and is specifically degraded by the mitochondrial protease Lon (20). Moreover, we demonstrated that the rate of PDK4 turnover is reduced in the presence of fatty acids, indicating that protein degradation represents a previously underappreciated facet of PDK4 regulation and, in effect, cardiac PDH activity and metabolic flexibility (20).…”
mentioning
confidence: 63%
“…Reductions in PDK4 protein content following transition to a low-fat diet indicate a role for PDK4 degradation. In a previous study, we demonstrated that degradation of PDK4 by the Lon protease requires dissociation of PDK4 from the PDH complex (20). We sought to determine metabolites that govern the inter-action of PDK4 with PDH and, ultimately, degradation of PDK4.…”
Section: Coash-dependent Pdk4/pdh Dissociation Promotes Pdk4 Degradationmentioning
confidence: 99%
See 1 more Smart Citation